Crystal and fluid modes in three-dimensional finite dust clouds - André Schella; Matthias Mulsow; André Melzer; Hanno Kählert; Dietmar Block; Patrick Ludwig; Michael Bonitz (New Journal of Physics, 2013)
The spectral properties of three-dimensional dust clusters confined in gaseous discharges are investigated using both a fluid mode description and the normal mode analysis (NMA). The modes are analysed for crystalline clusters as well as for laser-heated fluid-like clusters. It is shown that even for clusters with low particle numbers and under presence of damping fluid modes can be identified. Laser-heating leads to the excitation of several, mainly transverse, modes. The mode frequencies are found to be nearly independent of the coupling parameter and support the predictions of the underlying theory. The NMA and the fluid mode spectra demonstrate that the wakefield attraction is present for the experimentally observed Yukawa balls at low pressure. Both methods complement each other, since NMA is more suitable for crystalline clusters, whereas the fluid modes allow to explore even fluid-like dust clouds.